(untitled) (Journal of Contemporary Educational Policies and Practices, 2024)
Education for Sustainable Development (ESD) necessitates a holistic and transformational approach that includes three dimensions: learning content, pedagogy, and learning outcomes. The integration of sustainable development (SD) into learning content and learning outcomes has attracted increasing attention; however, pedagogy for SD has hardly been examined. This study examines how didactic approaches which are utilized at a teacher education institution (TEI), specifically, Hanoi National University of Education, connect to sustainability competencies. The analysis is based on the theoretical framework and relevant literature in ESD. The results reflect that half of the current didactic approaches at HNUE can promote sustainability competencies at different levels (likely, maybe, and unlikely) with the prevalence of the ‘maybe’ level. The other approaches are not known to be broadly used in promoting sustainability competencies. This study offers implications for TEIs in advancing their contribution to ESD, especially, in reconsidering didactic approaches to develop sustainability competencies and promote action-oriented, learner-centered, and transformative learning.